All Common Tangents

Level pending

The parabolas x 2 + 2 x y + y 2 + 2 x 2 y = 0 x^2 + 2xy + y^2 + \sqrt{2}x - \sqrt{2}y = 0 and x 2 + 2 x y + y 2 2 x + 2 y + 8 = 0 x^2 + 2xy + y^2 - \sqrt{2}x + \sqrt{2}y + 8 = 0 have common tangents at P P and Q Q and R R and S S .

If the total area A R 1 + R 2 A_{R_{1} + R_{2}} of the regions above can be expressed as A R 1 + R 2 = a b c A_{R_{1} + R_{2}} = \dfrac{a\sqrt{b}}{c} , where a , b a,b and c c are coprime positive integers, find a + b + c a + b + c .


The answer is 21.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Dec 10, 2019

Using the equations of rotation for a rotation about the origin ( 0 , 0 ) : (0,0) :

x = x cos ( θ ) y sin ( θ ) x = x'\cos(\theta) - y'\sin(\theta)

y = x sin ( θ ) + y cos ( θ ) y = x'\sin(\theta) + y'\cos(\theta)

Replacing x x and y y in x 2 + 2 x y + y 2 + 2 x 2 y = 0 x^2 + 2xy + y^2 + \sqrt{2}x - \sqrt{2}y = 0 and finding θ \theta we obtain:

x 2 + y 2 + ( x 2 y 2 ) sin ( 2 θ ) + 2 cos ( 2 θ ) x y + 2 ( cos ( θ ) sin ( θ ) ) x 2 ( sin ( θ ) + cos ( θ ) ) y = 0 x'^2 + y'^2 +(x'^2 - y'^2)\sin(2\theta) + 2\cos(2\theta)x'y' + \sqrt{2}(\cos(\theta) - \sin(\theta))x' - \sqrt{2}(\sin(\theta)+ \cos(\theta))y' = 0

Setting x y x'y' term to zero we have cos ( 2 θ ) = 0 2 θ = π 2 θ = π 4 \cos(2\theta) = 0 \implies 2\theta = \dfrac{\pi}{2} \implies \theta = \dfrac{\pi}{4}

2 x 2 2 y 2 = 0 y = x 2 \implies 2x'^2 - 2y'^2 = 0 \implies \boxed{y' = x'^2} .

In a similar manner replacing x x and y y in x 2 + 2 x y + y 2 2 x + 2 y + 8 = 0 x^2 + 2xy + y^2 - \sqrt{2}x + \sqrt{2}y + 8 = 0 we obtain: y = x 2 4 \boxed{y' = -x'^2 - 4}

Let f ( x ) = x 2 f(x') = x'^2 and g ( x ) = x 2 4 g(x') = -x'^2 - 4 f ( a ) = 2 a = g ( b ) = 2 b a = b \implies f'(a) = 2a = g'(b) = -2b \implies a = -b .

Let R : ( b , b 2 ) R:(-b,b^2) and S : ( b , b 2 4 ) m R S = 2 b 2 + 4 2 b = 2 b S:(b,-b^2 - 4) \implies m_{RS} = \dfrac{2b^2 + 4}{-2b} = - 2b

2 b 2 4 = 0 b = ± 2 \implies 2b^2 -4 = 0 \implies b = \pm\sqrt{2} .

In the x y x'y' system:

For b = 2 R : ( 2 , 2 ) b = \sqrt{2} \implies R:(-\sqrt{2},2) and S : ( 2 , 6 ) S:(\sqrt{2},-6)

and

For b = 2 P : ( 2 , 2 ) b = -\sqrt{2} \implies P:(\sqrt{2},2) and Q : ( 2 , 6 ) Q:(-\sqrt{2},-6)

For region R 1 : R_{1}: R P = 2 \overleftrightarrow{\rm RP} = 2 and f ( x ) = x 2 f(x') = x'^2

A R 1 = 2 2 ( 2 x 2 ) d x = \implies A_{R_{1}} = \displaystyle\int_{-\sqrt{2}}^{\sqrt{2}} (2 - x'^2) dx = ( 2 x x 3 3 ) 2 2 = 8 2 3 (2x' - \dfrac{x'^3}{3})|_{-\sqrt{2}}^{\sqrt{2}} = \dfrac{8\sqrt{2}}{3} .

For region R 2 : R_{2}: Q S = 6 \overleftrightarrow{\rm QS} = -6 and f ( x ) = x 2 4 f(x') = -x'^2 - 4

A R 1 = 2 2 ( 2 x 2 ) d x = A R 1 = 8 2 3 \implies A_{R_{1}} = \displaystyle\int_{-\sqrt{2}}^{\sqrt{2}} (2 - x'^2) dx = A_{R_{1}} = \dfrac{8\sqrt{2}}{3}

A R 1 + R 2 = 16 2 3 = a b c a + b + c = 21 \implies A_{R_{1} + R_{2}} = \dfrac{16\sqrt{2}}{3} = \dfrac{a\sqrt{b}}{c} \implies a + b + c = \boxed{21}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...